Dab1‐mediated colocalization of multi‐adaptor protein CIN85 with Reelin receptors, ApoER2 and VLDLR, in neurons. (19th March 2013) - Fuchigami, Takahiro; Sato, Yutaka; Tomita, Yuya; Takano, Tetsuya; Miyauchi, Shin‐ya; Tsuchiya, Yukinori; Saito, Taro; Kubo, Ken‐ichiro; Nakajima, Kazunori; Fukuda, Mitsunori; Hattori, Mitsuharu; Hisanaga, Shin‐ichi
<x xml:space="preserve">Abstract</x> Reelin‐Dab1 signaling is indispensable for proper positioning of neurons in mammalian brain. Reelin is a glycoprotein secreted from Cajal‐Reztuis cells in marginal zone of cerebral cortex, and its receptors are Apolipoprotein E receptor 2 (ApoER2) or very low density lipoprotein receptor (VLDLR) expressed on migrating neurons. When Reelin binds to ApoER2 or VLDLR, an adaptor protein Dab1 bound to the receptors undergoes Tyr phosphorylation that is essential for Reelin signaling. We reported previously that Cdk5‐p35 phosphorylates Dab1 at Ser400 and Ser491 and the phosphorylation regulates its binding to CIN85, which is an SH3‐containing multiadaptor protein involved in endocytic downregulation of receptor‐tyrosine kinases. However, the interaction of CIN85 with Dab1 has not been addressed in neurons. We examined here a possibility that CIN85 has a role in Reelin signaling. We found nonpho‐sphorylated Dab1‐mediated colocalization of CIN85 with ApoER2. The colocalization of CIN85 with ApoER2 was increased in neurons stimulated with Reelin repeats 3‐6, an active Reelin fragment. The stimulation recruited CIN85 to domains in plasma membrane where it colocalized with ApoER2 and Dab1 and then to EEA1‐labeled early endosomes in the cytoplasm. In addition, Tyr phosphorylation of Dab1 strengthened the binding to CIN85. These results suggest that CIN85 participates in Reelin signaling through the binding to Dab1.